ANALISIS MANAJEMEN RISIKO PEMBIAYAAN GADAI EMAS DI BSI KCP SLEMAN 1 YOGYAKARTA - Anggraini, Anisa Nur; Ilmiah, Dunyati (Journal Of Islamic Ekonomic and Business, 2022)
Gold pawn financing is a financing product offered by Islamic banks with the aim of consumptive and productive activities with murabahah/Musyarakah Mutanaqishah/Ijarah contracts with collateral in the form of gold tied to a rahn contract, which will be deposited by the bank for a certain period of time. The purpose of this study is to find out how risk management is in gold pawn financing at Bank Syariah Indonesia during the covid 19 pandemic. This research uses the type of qualitative research. The subject of this research is Bank Syariah Indonesia KCP Sleman 1. The object of this research is risk management on gold pawn financing at Bank Syariah Indonesia KCP Sleman 1. The data obtained in this study are the results of interviews, observations and documentation. The results of the study indicate that there are several risks faced by Bank Syariah Indonesia KCP Sleman 1 including: credit risk, market risk, operational risk and marketing risk. To minimize this risk, it is necessary to implement risk management. Risk management carried out by Bank Syariah Indonesia KCP Sleman 1 includes: Risk Identification, Risk Measurement, Risk Monitoring and Risk Control.